Improving energy storage ability of ammonium-decorated cobalt fluoride using selenization as efficient active material of supercapacitor. (20th October 2022) - Wu, Yung-Fu; Cao, Yu-Cheng; Lee, Pin-Yan; Kubendhiran, Subbiramaniyan; Chung, Ren-Jei; Yougbaré, Sibidou; Lin, Lu-Yin
Abstract: Zeolitic imidazolate framework-67 (ZIF67) derivatives with high surface area, pore volume and multiple redox states of cobalt are regarded as one of promising electroactive materials of supercapacitors (SC). A novel ZIF67 derivative synthesized with ammonia fluoride in our previous work shows an excellent energy storage ability due to favorable morphology and efficient charge transportation. In addition, cobalt selenide having multiple redox states and high electronegativity favors pseudocapacitive electron storage and charge transportation. In this study, NH4 F-induced ZIF67 derivatives are firstly selenized using a one-step annealing process with Se powder as electroactive material of SC. Different selenization temperatures are applied to optimize the electrochemical performance. The selenized NH4 F-induced ZIF67 derivative synthesized using 400°C presents the largest specific capacitance of 475.8 F/g at 20 mV/s, due to the smallest particle size and suitable fluoride/selenide composition. The symmetric SC comprising optimal selenized NH4 F-induced ZIF67 derivative electrodes presents a maximum energy density of 2.8 Wh/kg at the power density of 400 W/kg, and the CF retention of 117% and Coulombic efficiency higher than 90% in 4000 charge/discharge cycles. The excellent energy storage ability achieved in this study suggests the practical applications of ammonia fluoride and selenization on ZIF67 for enhancing the electrochemical performance. Graphical abstract: Image, graphical abstract